Functional Characteristics Enhancement of Austenitic Stainless Steel (Ss-316 L) Through Microwave Hybrid Heating - Singh, Dilkaran (My University, 2018)
The primary objective of the present study was to develop a wear resistant cladding on austenitic stainless steel (SS-316 L) substrate through microwave hybrid heating technique. Austenitic stainless steel is widely used in almost every manufacturing industries. This can be attributed to their exceptional corrosion resistance. However, this grade of stainless steel are deprived of wear resistance properties when exposed under severe wear working conditions. The failure of these materials cause huge economical loss to developing countries like India. The wear performance of austenitic stainless steel can be improved by coating/cladding the surface of steels with wear resistant materials. Microwave energy has emerged as a novel material processing technique in the past years. The clads of Ni-based20WC8Co-10Mo and Ni-based10WC8Co-10Cr3C2 powder compositions were successfully developed on austenitic stainless steel (SS-316 L) substrate using multimode domestic microwave oven working at frequency of 2.45 GHz. Microwave exposure time and power level were selected as the process parameters. The process parameters were optimized to get good metallurgically bonded clads. The developed clads were further characterized through various relevant techniques like scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), dry sliding wear test, Vickers microhardness test and flexural strength test.The SEM images revealed the thickness of the developed clads to be 1 mm approximately. The developed clads were free from any type of cracks and porosity. The presence of Fe in the clad region supported and verified the claim of metallurgical bonding between the clad and substrate. The magnified image of the clad region showed the presence of hard carbide particles randomly distributed in the clad region. These hard carbide particles were responsible for increasing the microhardness value of the developed clads which was measured to be 503 ± 34 Hv for Ni-based10WC8Co-10Cr3C2 clad and 752 ± 34 Hv for Ni-based20WC8Co-10Mo clad.
Keywords: Microwave Heating; Characterization; Metal Matrix Composite; Microhardness; Cladding